(untitled) (Quinto Sol, 2013)
This paper deals with the process of the settlement in a zone of the south frontier of Buenos Aires province, the Azul brook one, which –differently from other areas of Buenos Aires field- was driven by the Provincial State of Buenos Aires throughout a sequence of conditioned donations of small and médium portions of lands which were developed by the Rosas government since 1830. These donations contributed to the settlement and the production labor of these lands by civil population that settled there and that generated relationships with the indigenous comunities established in the zone, who were articulated to the policy of the “negocio pacífico de indios” (“pacific deal of indians”).